Enter a problem...
Algebra Examples
F=kqQr2
Step 1
Rewrite the equation as k(qQr2)=F.
k(qQr2)=F
Step 2
Combine k and qQr2.
kqQr2=F
Step 3
Multiply both sides by r2.
kqQr2r2=Fr2
Step 4
Step 4.1
Cancel the common factor of r2.
Step 4.1.1
Cancel the common factor.
kqQr2r2=Fr2
Step 4.1.2
Rewrite the expression.
kqQ=Fr2
kqQ=Fr2
kqQ=Fr2
Step 5
Step 5.1
Divide each term in kqQ=Fr2 by qQ.
kqQqQ=Fr2qQ
Step 5.2
Simplify the left side.
Step 5.2.1
Cancel the common factor of q.
Step 5.2.1.1
Cancel the common factor.
kqQqQ=Fr2qQ
Step 5.2.1.2
Rewrite the expression.
kQQ=Fr2qQ
kQQ=Fr2qQ
Step 5.2.2
Cancel the common factor of Q.
Step 5.2.2.1
Cancel the common factor.
kQQ=Fr2qQ
Step 5.2.2.2
Divide k by 1.
k=Fr2qQ
k=Fr2qQ
k=Fr2qQ
k=Fr2qQ